Facile preparation of hydroxyl bearing covalent organic frameworks for analysis of phenoxy carboxylic acid pesticide residue in plant-derived food. (30th May 2021) - Xu, Guiju; Hou, Longfei; Li, Baoyu; Wang, Xiaoli; Liu, Lu; Li, Na; Wang, Ming-Lin; Zhao, Ru-Song
Highlights: An ultrasensitive method was established for the determination of PCAs residue in plant-derived food. The TAPT-DHTA-COF fabricated via room-temperature method was proposed as SPE cartridge packing. The adsorption feature was discussed by isotherm model fitting and theoretical calculation. The reliability of this method was verified by the accurate detection of certified reference materials. Abstract: The development of sensitive method for analysis of pesticide residue is of great significance to ensure food safety and promote globalization of food trade. An original method was proposed for analysis of phenoxy carboxylic acids (PCAs) pesticide in plant-derived food. To concentrate trace PCAs, the TAPT-DHTA-COF was fabricated by a facile room-temperature method and utilized as the solid phase extraction cartridge packing. The TAPT-DHTA-COF exhibited excellent adsorption capacity and recyclability towards PCAs. Theoretical simulation indicated that the adsorption of PCAs onto the TAPT-DHTA-COF was driven by hydrogen bond, halogen bond and π-π interaction. Using liquid chromatography tandem mass spectrometry for detection, good linearity ranged from 0.10 to 40 ng·g −1 and low limits of detection varied from 0.007 to 0.030 ng·g −1 were achieved for PCAs in rice, apple and greengrocery. The recoveries of PCAs from the spiked samples ranged from 81.2% to 107%. The reliability was verified by the accurate determination of certified reference materials.